2017
DOI: 10.1016/j.jsha.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Components and determinants of therapeutic delay in patients with acute ST-elevation myocardial infarction: A tertiary care hospital-based study

Abstract: The standard of STEMI management in our state is far from ideal, and calls for a lot of improvement. Major efforts to reduce prehospital and in-hospital treatment delays are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 28 publications
5
35
0
1
Order By: Relevance
“…Proper reperfusion is done by thrombolysis or primary PCI which can decrease the size of infract, protect the left ventricle and improve the longterm and short-term consequences of disease. 5,6 Doing primary PCI is the strategy of selective reperfusion in STEMI patients and when it is done urgently and in first hours of MI, it is effective in re-establishment of blood flow and this method is useful for patients with contraindication of fibrinolytic therapy. It seems that this method is more effective than fibrinolysis in bypassing clogged arteries and when it is done by experienced stuff and in specialized centers, it will be with long-term and short-term results.…”
Section: Introductionmentioning
confidence: 99%
“…Proper reperfusion is done by thrombolysis or primary PCI which can decrease the size of infract, protect the left ventricle and improve the longterm and short-term consequences of disease. 5,6 Doing primary PCI is the strategy of selective reperfusion in STEMI patients and when it is done urgently and in first hours of MI, it is effective in re-establishment of blood flow and this method is useful for patients with contraindication of fibrinolytic therapy. It seems that this method is more effective than fibrinolysis in bypassing clogged arteries and when it is done by experienced stuff and in specialized centers, it will be with long-term and short-term results.…”
Section: Introductionmentioning
confidence: 99%
“…More than fifty percentage of the patients age ranges from 45-65 yrs with mean of 60 yrs (SD=13.02) which is similar to the study by Perkins-Porras L. et al, [11] Beig JR. et al, [12] and Ribeiro S. et al, [13] where mean age was 59 (SD=11.2), 57.6 (SD=10.5), and 62 yrs (SD=13.64) respectively. Whereas, a study conducted in China reported the mean age of the patient was found to be 65.68 yrs (SD=12.68).…”
Section: Discussionmentioning
confidence: 99%
“…[19,20] However, few studies showed significantly lower door to needle time i.e 40 min and 34 min respectively. [12,21] The current study enlightened the most commonly used thrombolytic agent was tenecteplase (TNK) 54.7%. Nevertheless, the study conducted in Mexico confirmed streptokinase as a most commonly used lytic agents in 67% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visiting non-qualified or under-qualified medical practitioners or drug sellers or taking self-medication significantly increased pre-hospital delay. Such a trend is also present in India where visiting non-qualified practitioner was found to increase the delay (32). Though medical practice by non-qualified persons are rare in developed countries, consultation with non-medical personnel for advice or self-medication (33) and visiting GPs (19,24) markedly prolonged the prehospital delay there.…”
Section: Pre-hospital Delaymentioning
confidence: 93%